Écrivez partout - Casiccia, Alessandro (Scenari, 2021)
This paper will review the role of language, of writing, of signs, in the protests of “sixty-eght” and in the changes in advanced capitalist countries from the second half of twenties century to now. The solidarity of the intellectual world with the movements in universities and in factories could not hidden the conflictual relationship between sartrian existentialism and post-stucturalist thought. But the movement had started some years earlier in the University of California; in it, the philosophers of Frankfurt School saw a reply to the deceptive forms of advanced capitalism. In Berkeley, as in Paris and everywere, became evident how problematic was to trace back the relationship between singns and their source, desires and the response to them, but even more between objects in their appearance and the moment of their production.